Testo scritto come l’input linguistico nella didattica dell’italiano LS - Kucharska, Anna (Neophilologica, 2017)
The aim of the article is to analyse the impact of theoretical knowledge of discussed argument on the structure, cohesion and linguistic variety of essays written by students — learners of Italian. The comparative study of twelve essays entitled “Il Made in Italy” composed by six students (the first one written spontaneously without substantial preparation, the second one after reading a theoretical fragment of a scientific paper concerning the topic of the essay) has provided some interesting observations regarding the types of used topics and comments as well as various sorts of logical relations present in the texts.